Sugar profile determination of four pure Greek honeys by gas-chromatography - TYRPENOU (Α.Ε.ΤΥΡΠΕΝΟΥ) A. E. (Journal of the Hellenic Veterinary Medical Society, 2018)
Honey sugar determination was performed by using a combination of two methods (Iverson & Bueno, 1981 and Pierce no. 16, 1990) with some modifications. The proposed by Pierce method no.16, has been designed to assist in the routine determination of sugars in food products and syrups. Sugars are treated with hydroxylamine hydrochloride and the resulting oximes are converted to trimethylsilyl ethers by direct silylation with TMS. The derivatives are then determined by gas-chromatography with flame ionization detector and sugar oxime-TMS derivatives are quantitative and reproducible. This reaction is fast and simple, the results are quantitatively reproducible and multiple peaks due to the tautomeric forms of reducing sugars, which produced by direct TMS derivatization, are eliminated. From the honey samples analyzed it has been determined that only fir-tree honey contains trisaccharides with higher percentages that of melezitose.